Method of photothermal tissue reconstruction in modern medical practice using ER:YAG laser - I A Kulikov; L B Spokoynyy; E A Gorbunova; I A Apolikhina (IP Berlin A.V., 2018)
This article is devoted to the review of domestic and foreign data on the efficacy and safety of non-invasive erbium laser therapy aimed at increasing the tone of the pelvic floor muscles. The search for literature data allowed to reveal a lot of studies describing the successful experience of non-invasive laser procedures in gynecology, as well as not only the high effectiveness of the method, but also its safety. This type of therapy represents a promising treatment technology with a high level of efficacy and an optimal safety profile.